Salt and fat contents in preparations at commercial restaurants in Goiânia-GO - Camila Silva Kunert; Mariana Patrício de Morais; Ana Clara Martins e Silva Carvalho (Universidade de Fortaleza, 2013)
Objective: To evaluate the sodium and fat contents added to preparations of commercialrestaurants in Goiânia-GO, Brazil. Methods: This was an observational, cross-sectionaland descriptive study. It included 'pay-per-weight' restaurants with a medium standardmenu and having as daily preparations white rice, beans and grilled chicken. Among theestablishments with these characteristics, three agreed to participate. The production processof the above-mentioned preparations was accompanied for three non-consecutive days ineach establishment. For quantification of sodium and fat added into the preparations, oiland salt were weighed, as well as the finished preparation; the weight of the standard portion and the yield of the preparation expressed in number of portions prepared were settled. From these data, the per capita amount of salt and oil added to cook one portion of each kind of preparation was calculated by dividing the total quantity of salt and oil by the number of prepared portions. Results: The levels of salt (3.0, 2.7, and 4.1 g - restaurant A, B and C,respectively) and oil (17.0, 11.3, and 11.2 g - restaurant A, B and C, respectively) added inthe three preparations are superior to the recommendations. Conclusion: The sodium andfat contents in the analyzed restaurants are higher than it is recommended by the Food Guidefor the Brazilian Population. It is essential that commercial restaurants become partners ofpublic policies on health promotion, adopting good nutritional practices, by reducing the sodium and fat contents, to offer healthy meals daily.